PROGETTO DI ISTITUZIONE DI DISTRETTI CULTURALI EUROPEI. IL DISTRETTO CULTURALE GOMOSAICO DI GORIZIA (Istituto Lombardo - Accademia di Scienze e Lettere • Rendiconti di Lettere, 2020)
It is here presented the hypothesis of establishing European cultural districts. Its purpose is to systematically valorize the cultural heritage of their territories end their people. The proposal is innovative with contribution to economic and civil life. A cultural district with Gorizia as capital is given as significant exemple. Its importance is that it originates from the tradition of ancient Aquileia and that is meeting point between three very important ethnic groups: Latin, German, Slavic. It is a district of symbolic value also for the enhancement of the strategic axis for Europa “Mitteleuropa-Mediterranean”.